Quality Control of Health Services of The National Health Insurance Era in East Java - Indonesia: Barriers and Strategy - Mardi Wibowo, Nugroho; Utari, Woro; Widiastuti, Yuyun; ., Abdul Muhith (KnE Social Sciences, 2023)
The National Health Insurance ( JKN) system is designed to provide the availability of quality health services, but until now JKN participant have not felt the quality health care. The purpose of this study is to identify threats and weaknesses in health care quality control and formulate the implications of its strategy. The study was conducted at four Regional General Hospital (RSUD) in East Java - Indonesia, namely RSUD IbnuSina Gresik, RSUD NgudiWaluyoWlingiBlitar, RSUD dr. H. SlametMartodirdjoPamekasan, and RSUD dr. H. KoesnadiBondowoso. The sampling of research samples was conducted by purposive sampling and data retrieval with questionnaires and interviews. Analysis techniques used are external factor analysis, internal factor analysis, and SWOT analysis. The results of the study found that the barriers to quality control of JKN health services are the delay in payment of hospital claims by the Social Security Regulatory Agencyof Health (BPJS Health), INA-CBGs rate, BPJS Health Regulations and low people awareness for a healthy lifestyle. In terms of internal hospitals, fraud prevention systems have not been affective. The implication of the strategy is that hospitals must develop and implement fraud prevention information systems properly. Keywords: JKN; BPJS; quality control; health services